Nitrogen-doped hollow carbon nanospheres for highly sensitive electrochemical sensing of nitrobenzene. (August 2018) - Liu, Mengjun; Zhang, Tongrui; Ren, Haoxuan; Wang, Lei; Meng, Tianjiao; Zhao, Jincan; Wang, Huan; Zhang, Yufan
Graphical abstract: N–doped hollow carbon nanospheres (NHCPs) were successfully prepared for using monodisperse silica microspheres (MSM) as a template and polydopamine (PDA) as carbon and nitrogen precursor by a nano hard-templating approach. Highlights: NHCPs were prepared using MSM as a template and PDA as carbon and nitrogen precursor. NHCPs-750 with high content of pyrindinic N showed good electrocatalytic performance. A sensitive electrochemical sensor for NB was developed based on the NHCPs-750–GCE. Abstract: Following hard template method, nitrogen–doped hollow carbon nanospheres (NHCPs) were successfully prepared by using monodisperse silica microspheres as a template and dopamine as carbon and nitrogen precursor. A series of NHCPs-x samples with different pyrolysis temperatures were reported. The composite material formation was characterized by detailed methods (e.g., X-ray photoelectron spectroscopy, Fourier transform infrared spectroscopy, scanning electron microscopy and transmission electron microscopy). Results indicated that NHCPs treated at 750 °C with highest amounts of pyrindinic N showed improved electro-catalytic activity for nitrobenzene (NB) in neutral solution. NHCPs-750 can be developed as an effective sensing platform for the detection of NB, which showed high activity and superior analytical performance, such as a wide linear range of 5–2610 μM, a high sensitivity of 436 μAmM −1, and a low limit of detection of 2.29 μM.